The Aesthetics of Eulogizing a Brother Among Classical Poets - Mohameed, Prof.Dr. Herish Mohammed Amin; Ismail, Asst.L. Tara Ismail Ahmed; Naji, Asst.L. Wirya Naji Abdullah (Sulaimani Journal for Humanities, 2025)
The research deals with the topic of “brother’s lament among veteran poets” in terms of how this painful experience affects the poet’s psyche and how it is reflected in their poetry. We surveyed this topic among a group of veteran poets. This research begins with an introduction in which we talked about lamentation, its importance, and the objectives of the research. Then we began with a preface in which we discussed the concept of lamentation linguistically and terminologically and talked about the image of lamentation among veteran poets. Then we divided the research into two sections. The first section we devoted to the types of lamentation (lamentation, eulogy, condolence). In Arabic poetry, we came up with poetic models and analyzed them. As for the second section, we talked about the brother’s lamentation among veteran poets. We referred to three of the distinguished veteran poets in the brother’s lamentation, namely (Duraid ibn al-Sammah, al-Khansa’, Tammam ibn Nuwayra and Labid bin Rabia Al-Amiri), and we analyzed several of their poetic verses.
Keywords: lamentation; lamentation; eulogy; condolences; veterans; brother